Evidence on the male marriage wage premium and cohabitation premium in Brazil - Guiginski, Janaína (2023)
The article aims to explore the correlation between marriage, cohabitation, and male labor income. It delves into the concept of the “male marriage wage premium” - a phenomenon where married men earn higher wages compared to single men in the labor market. Since consensual unions are prevalent in Brazil, the study also examines the cohabitation premium. The research employs linear regressions, quantile regression, and Blinder-Oaxaca decompositions of earnings differentials between single, married, and cohabiting men to analyze the association between marital status and paid work among Brazilian men. The data utilized were from the 2010 Demographic Census. The results of the study validate the existence of marriage and cohabitation premia for Brazilian men. However, the observed premium tend to be lower for cohabitation than for marriage. The decompositions reveal that these differentials are due to wage structure and not composition effects.